Medicinal plants used in the treatment of dyslipidemias: an integrative review (Research, Society and Development, 2022)
The study aimed to carry out a literature review to qualitatively evaluate the potential of medicinal plants in the treatment and control of dyslipidemias. It was an integrative review in the electronic databases VHL (Virtual Health Library), Scielo (Scientific Electronic Analysis and Retrieval) and PubMed. We searched for articles distributed between 2011 and 2021, published in English and Portuguese. Results: 123 articles were identified and after careful screening, 46 articles were read in their entirety, 28 studies were discarded for not meeting the required criteria, leaving 18 articles selected for the present work. The data obtained were arranged in a chronological and descriptive table for further analysis. Results: the most cited plants were Ilex paraguariensis and Camponesia xanthorcapa. In terms of cholesterol reduction, the plant that obtained the best results was Bixa orellana L. (urucum). In terms of LDL reduction, the best performance was achieved by Butia odorata (butiá) which also had the best result in reducing triglycerides. As for HDL, a helping molecule in the fight against atherosclerosis, the plant that best caused an increase in this was Camellia sinenis (Indian tea). Conclusion: the results that were obtained in the study prove the lipid-lowering capacity of medicinal plants. These can be an important alternative for the prevention of hyperlipidemia, as well as an excellent complement in the conventional treatment of the disease. Further studies that can cover this theme are recommended to corroborate the effectiveness of these plants.